Microenvironment-Dependent Phenotypic Changes in a SCID Mouse Model for Malignant Mesothelioma - Darai-Ramqvist, Eva; Nilsonne, Gustav; Flores-Staino, Carmen; Hjerpe, Anders; Dobra, Katalin (Frontiers in Oncology, 2013)
Background and Aims: Malignant mesothelioma is an aggressive, therapy-resistant tumor. Mesothelioma cells may assume an epithelioid or a sarcomatoid phenotype, and presence of sarcomatoid cells predicts poor prognosis. In this study, we investigated differentiation of mesothelioma cells in a xenograft model, where mesothelioma cells of both phenotypes were induced to form tumors in SCID mice. Methods: Xenografts were established and thoroughly characterized using a comprehensive immunohistochemical panel, array comparative genomic hybridization of chromosome 3, fluorescent in situ hybridization and electron microscopy. Results: Epithelioid and sarcomatoid cells gave rise to xenografts of similar epithelioid morphology. While sarcomatoid-derived xenografts had higher growth rates, the morphology and expression of differentiation-related markers was similar between xenografts derived from both phenotypes. Array comparative genomic hybridization showed a convergent genotype for both xenografts, resembling the original aggressive sarcomatoid cell sub-line. Conclusions: Human mesothelioma xenografts from sarcomatoid and epithelioid phenotypes converged to a similar differentiation state, and genetic analyses suggested that clonal selection in the mouse microenvironment was a major contributing factor. This thoroughly characterized animal model can be used for further studies of molecular events underlying tumor cell differentiation.